2017
DOI: 10.1126/sciadv.1602321
|View full text |Cite
|
Sign up to set email alerts
|

Comment (1) on “Formation of the Isthmus of Panama” by O’Dea et al .

Abstract: The conclusions of O’Dea et al. on the formation of the Isthmus of Panama are not supported by analysis of the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 30 publications
1
64
0
1
Order By: Relevance
“… 0–15 Ma: From the Middle Eocene to the Holocene, landmasses had approximately occupied their current position. The Central American Seaway between South America and the Panama Bloc was fully closed by 15–13 Ma (Jaramillo et al., ; Montes et al., ) facilitating biotic interchange between North and South America as shown for wide range of taxonomic groups in Bacon et al. ().…”
Section: Methodsmentioning
confidence: 99%
“… 0–15 Ma: From the Middle Eocene to the Holocene, landmasses had approximately occupied their current position. The Central American Seaway between South America and the Panama Bloc was fully closed by 15–13 Ma (Jaramillo et al., ; Montes et al., ) facilitating biotic interchange between North and South America as shown for wide range of taxonomic groups in Bacon et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…13–15 Ma, Montes et al., ), and its complete and final closure in the early Pliocene ( c . 3–4 Ma, Jaramillo et al., ; Leigh, O'Dea, & Vermeij, ; Weir, Bermingham, & Schluter, ). Furthermore, the Andean Cordillera acted as a connecting bridge between northern and southern South America for arctic flora during warm periods (Ball, ; Moore & Chater, ; Vollan, Heide, Lye, & Heun, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the Northern Hemisphere, glacial periods produced the closure of the Bering Strait and the appearance of the Beringian land bridge which connected Asia and North America (Brikiatis, 2014) as a result of ice formation and a drop in sea level (Hopkins, 1972). The connection of North and South America was marked by the formation of the Isthmus of Panama in the late Ma, Montes et al, 2015), and its complete and final closure in the early Pliocene (c. 3-4 Ma, Jaramillo et al, 2017;Leigh, O'Dea, & Vermeij, 2014;Weir, Bermingham, & Schluter, 2009). Furthermore, the Andean Cordillera acted as a connecting bridge between northern and southern South America for arctic flora during warm periods (Ball, 1990;Moore & Chater, 1971;Vollan, Heide, Lye, & Heun, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This supports the hypothesis that lowland white sand areas may be where many Neotropical lineages first began to diversify(Frasier, Albert, & Struwe, 2008). The timing of this event has been much debated with most recent studies placing it in the early Miocene (e.g.,Montes et al, 2015) that has been supported by studies using dated phylogenies to suggest support for an earlier direct land connection (e.g.,Bacon et al, 2015aBacon et al, , 2015bBacon, Mora, Wagner, & Jaramillo, 2012;De Baets, Antonelli, & Donoghue, 2016;Jaramillo et al, 2017;Smith, Amei, & Klicka, 2012). A dated phylogeny of the families Bromeliaceae and Rapateaceae that are either epiphytic or largely restricted to sandstone substrates indicated that these families first evolved at low elevations in the Guayana Shield before extending their distributions more broadly throughout South America and into Africa(Givnish et al, 2004).…”
mentioning
confidence: 99%